PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SD SWASTA KATOLIK BUDI MURNI 2 MEDAN - Tua Yohana Sinaga; Eka Margareta Sinaga; Frikson Jony Purba; Dyan Wulan Sari HS; Anton Sitepu; Patri Janson Silaban (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Make A Match type cooperative learning model on student learning outcomes in Mathematics subjects on measuring and comparing angles in class VA of Budi Murni 2 Medan Private Catholic Elementary School in the 2024/2025 Academic Year. The Independent Variable in this study is the Make A Match type Cooperative Learning Model (X) and the Dependent Variable in this study is Student Learning Outcomes (Y). The research method used is Quantitative Pre-Experiment Type, the population of this study was all fifth grade students of Budi Murni 2 Medan Private Catholic Elementary School, totaling 4 classes. Sampling using Probability Sampling Type Simple Random Sampling with a sample of all VA class students of Budi Murni 2 Medan Private Catholic Elementary School totaling 36 students. To determine the initial abilities of students, the researcher conducted a Pretest with an average value of 59.25 in the incomplete category. After the researcher used the Make A Match type Cooperative Learning Model, it showed that student learning outcomes increased in the Posttest with an average value of 76.42 in the complete category. The success rate of student learning outcomes has increased as evidenced by the results of the Correlation Test calculation obtained of 0.603, which means that rcount (0.603) > rtable (0.329). Furthermore, the Hypothesis test (t-test) where tcount > ttable is (4.404) > (2.035) so that it can be stated that Ha is accepted and Ho is rejected. This shows that there is a significant influence of the use of the Make A Match type Cooperative Learning Model on the Mathematics learning outcomes of students in the material